Micromechanical model for 3D generally orthotropic grid-reinforced composites - Hassan, Essmat M.; Kalamkarov, Alexander L.; Georgiades, Tasos (My University, 2009)
A micromechanical model for 3D composites with an embedded periodic grid of generally orthotropic reinforcements is developed and applied to anisotropic structures with cubic, conical and diagonal reinforcement orientations to calculate effective elastic coefficients. The model allows flexibility in the design of such structures with desirable coefficients by changing material and/or geometric parameters.
Keywords: Micromechanics; Elasticity; Hygrothermoelasticity